China tuberculosis policy at crucial crossroads: comparing the practice of different hospital and tuberculosis control collaboration models using survey data. - Xiaolin Wei; Guanyang Zou; John Walley; Jia Yin; Knut Lonnroth; Mukund Uplekar; Weibing Wang; Qiang Sun (PLoS ONE)
Background Currently three hospital and tuberculosis (TB) collaboration models exist in China: the dispensary model where TB has to be diagnosed and treated in TB dispensaries, the specialist model where TB specialist hospital also treat TB patients, and the integrated model where TB diagnosis and treatment is integrated into a general hospital. The study compared effects of the three models through exploring patient experience in TB diagnosis and treatment. Methods We selected two sites in each model of TB service in four provinces of China. In each site, 50 patients were selected from TB patient registries for a structured questionnaire survey, with a total of 293 patients recruited. All participants were newly registered uncomplicated TB cases without any major complications or resistance to first-line anti-TB drugs, and having successfully completed treatment. Diagnostic and treatment procedures were reviewed from medical charts of the surveyed patients to compare with national guidelines. Results Specialist sites had the highest patient expenditure, hospitalization rates and mostly used second-line anti-TB drugs, while the integrated model reported the opposite. The median health expenditure was USD 1,499 for the specialist sites and USD 306 for the integrated sites, with 83% and 15% patients respectively having unnecessary hospitalization. 74% of the specialist sites and 19% of the integrated sites used second-line anti-TB drugs. Mixed results were identified in the two dispensary sites. One site had median health expenditure of USD 138 with 12% of patients hospitalized, while the other had USD 912 and 65% respectively. Conclusion The study observed prohibitive financial expenditure and a high level of deviation from national guidelines in all sites, which may be related to the profit-seeking behavior of public hospitals. The study supports the integrated model as the better policy option for future TB health reform in China.